2020
DOI: 10.1063/5.0030091
|View full text |Cite
|
Sign up to set email alerts
|

Polarization dependent photoluminescence and optical anisotropy in CuPtB-ordered dilute GaAs1–xBix alloys

Abstract: The GaAs1-xBix semiconductor alloy allows to achieve large bandgap reduction and enhanced spin-orbit splitting energy at dilute Bi quantities. The bismide is currently being developed for near-to midinfrared lasers, multi-junction solar cells, and photodetectors. In this structure-property relationship study of GaAsBi alloys, we report polarization dependent photoluminescence that reaches ratio up to 2.4 at room temperature. Polarization dependence is also presented using transmittance spectra, and also birefr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…[15] The importance of optical techniques when applied to MBE-grown GaAsBi alloys is also confirmed through remarkable experiments investigating strain-engineered bismides deposited on thin step-graded InGaAs buffer layers, [35] exploiting the relationships of polarized photoluminescence measurements with the bulk ordering. [36,37] The use of strain-engineering to tune the electronic properties of matter and then customize solid-state materials via a controlled deformation, offers intriguing possibilities to modulate the band structure and consequently ignite new electronic and optical properties, as in 2D materials [38,39] and in quantum dots. [40] Optical techniques (RAS, [15,17] photoluminescence [35][36][37] ) provide the opportunity of measuring directly and in a quite simple way the strain condition present in the sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] The importance of optical techniques when applied to MBE-grown GaAsBi alloys is also confirmed through remarkable experiments investigating strain-engineered bismides deposited on thin step-graded InGaAs buffer layers, [35] exploiting the relationships of polarized photoluminescence measurements with the bulk ordering. [36,37] The use of strain-engineering to tune the electronic properties of matter and then customize solid-state materials via a controlled deformation, offers intriguing possibilities to modulate the band structure and consequently ignite new electronic and optical properties, as in 2D materials [38,39] and in quantum dots. [40] Optical techniques (RAS, [15,17] photoluminescence [35][36][37] ) provide the opportunity of measuring directly and in a quite simple way the strain condition present in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…[36,37] The use of strain-engineering to tune the electronic properties of matter and then customize solid-state materials via a controlled deformation, offers intriguing possibilities to modulate the band structure and consequently ignite new electronic and optical properties, as in 2D materials [38,39] and in quantum dots. [40] Optical techniques (RAS, [15,17] photoluminescence [35][36][37] ) provide the opportunity of measuring directly and in a quite simple way the strain condition present in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…[ 30,31 ] An intriguing explanation is the presence of CuPt ordering in the bulk, naturally inducing optical anisotropy for light at normal incidence on the (001) plane. The existence of such a CuPt ordering in MBE grown GaAsBi samples has been reported in literature: [ 37–39 ] some of these papers remarkably present results of optical spectroscopy techniques. [ 37,38 ]…”
Section: Discussionmentioning
confidence: 99%
“…The existence of such a CuPt ordering in MBE grown GaAsBi samples has been reported in literature: [ 37–39 ] some of these papers remarkably present results of optical spectroscopy techniques. [ 37,38 ]…”
Section: Discussionmentioning
confidence: 99%
“…Dilute Bi compound semiconductors [ 1,2 ] have attracted much attention owing to their unique characteristics such as bandgap narrowing, [ 2–4 ] a temperature‐independent bandgap, [ 5 ] Auger effect suppression, [ 6 ] and improved crystal quality due to the surfactant effects of Bi. [ 7 ] The most commonly investigated dilute bismide system is GaAsBi, [ 8–18 ] and several research groups have demonstrated GaAsBi laser diodes. [ 19,20 ] Although there has been less research on dilute bismides in the InP system, [ 21–23 ] this system is important for longer‐wavelength applications such as fiber optic communications and infrared optics sensing.…”
Section: Introductionmentioning
confidence: 99%